Analisis Kemampuan Mahasiswa PGSD dalam Merancang Pembelajaran Berdiferensiasi di Sekolah Dasar - Golkardi Golkardi; Eti Kusuma; Dhini Mufti (Lembaga Yasin AlSys, 2026)
The diversity of elementary school students’ characteristics requires prospective teachers to have the ability to design instruction that is responsive to students’ learning needs. This study aims to analyze the ability of Primary School Teacher Education (PGSD) students to design differentiated instruction in elementary schools. This study used a quantitative approach with a descriptive method. The research participants consisted of 80 PGSD students who had taken courses in instructional planning, learning strategies, or microteaching. Data were collected through questionnaires and assessment sheets for differentiated instructional designs. Data were analyzed using descriptive statistics in the form of frequencies, percentages, means, and standard deviations. The results showed that PGSD students’ ability to design differentiated instruction was in the high category, with an overall mean of 72.11. The highest ability was found in the aspect of formulating learning objectives, while the lowest ability was found in the aspect of designing learning assessments. These findings indicate that students already have a sound pedagogical foundation but still require strengthening in developing product differentiation and assessments that are appropriate to students’ characteristics. The conclusion of this study affirms the importance of strengthening differentiated instructional planning competence for prospective elementary school teachers. The implications of this study include strengthening the courses of instructional planning, learning evaluation, and microteaching so that they are more integrated with differentiated instructional practices relevant to students’ needs.